Eye-Gaze Training Does Not Impact Performance on a Nonverbal Test of Reading Abilities for Children with Special Educational Needs - SHARON ARNOLD (Journal of Developmental and Physical Disabilities, 2024)
Many individuals in special education have difficulty with language, and little is known about their reading abilities due to challenges presented for assessment. A nonverbal word recognition test based was developed by Measuring the word recognition abilities of children who are (2019), which proved more sensitive than traditional reading tests. The current Experiment 1 replicated that result for children in special education, and noted that the modified reading test was especially sensitive for those who do not score well in traditional versions of reading and language assessments. However, removing the motor response required by the digitised response, in favour of using eye-tracking responses, did not aid assessment of reading performance. Experiment 2 tested the notion that it could be that participants unfamiliar with use of eye gaze tracking facilities may not respond well to such a test. Reading scores for two groups of pupils in special education were compared: a group who took part in ‘primer activities’ designed to encourage familiarity with eye gaze tracking, and a group who received no such intervention. There was no impact of eye gaze training on the results of the eye-gaze modulated modified nonverbal reading test, suggesting that manual responses are the most effective way of assessing word recognition.